Chondroitin sulfate produces antinociception and neuroprotection in chronic constriction injury-induced neuropathic pain in rats by increasing anti-inflammatory molecules and reducing oxidative stress - Olaseinde, Olutayo Folajimi; Owoyele, Bamidele Victor (International Journal of Health Sciences, 2021)
Objectives: Damage to the peripheral and central nervous system lead to Neuropathic pain (NP) which is a widespread and devitalizing condition. chondroitin sulfate (CS), has been used in managing joint pain and osteoarthritis. In this study, the effectiveness of CS on NP induced by chronic constriction injury (CCI) is examined. Methods: Thirty Wistar rats were distributed at random into six groups (n = 5). Sciatic nerve ligation was carried out by encircling the nerve with four loose ligatures to induce NP. Allodynia (cold and mechanical) and heat hyperalgesia were assessed using Acetone, von Frey filament and Hot plate tests. CCI induction resulted to NP, prominent from the 3rd day after surgery. Structural architecture of sciatic nerves was evaluated via histological examination of the transverse section of the nerves. Results: Oral administration of CS (600 mg/kg and 900 mg/kg for 21 days) resulted in significant (P < 0.05) inhibition of allodynia (cold and mechanical) and thermal hyperalgesia. Lipid peroxidation, tumor necrosis factor-α (TNF-α), calcitonin gene related peptide (CGRP), C reactive protein (CRP), and oxidative stress were attenuated by CS. CS also improved interleukin (IL)-6, nitric oxide (NO), total antioxidant capacity (TAC). Conclusion: These findings suggest that CS attenuates allodynia, and thermal hyperalgesia induced by CCI by downregulating TNF-α, CRP, CGRP, oxidative enzymes, and upregulating IL-6, NO, and TAC. Nociceptive behavioral studies and histological findings showed significant improvement in the CS treated groups compared to CCI rats. These findings are responsible for the beneficial effect of CS in NP.